The spatial variation of the efficiency of health services in the district of Khabat - Hashim Yaseen Hamadamin; Hoshmand Jawhar Abbas; Sangar Ahmed Hussein; Farhad Othman Omer (Zanco Journal of Humanity Sciences)
Health services is one of the activities and services that directly affect human life and the various settlements, and it has an active role in all fields of life. It is a clear indicator of human development in general and health development in particular. Therefore, responsible authorities and local and international health and humanitarian organizations must work in a new way to develop them. In order to provide the best health services and obtain them easily and equally for all members of society without discrimination.The main objective of the research is to show how the distribution and efficiency of health services and spatial analysis of health centers in the district of Khabat, According to the health services data for 2019. It is worth mentioning that the research includes three axes, the first: the spatial distribution of health services, and the second: the spatial analysis of health centers in the study area, and the third: We discussed the functional efficiency of health services in the elimination of disappointments and the evaluation of services in terms of providing them fairly to the residents of the study area according to administrative units, and according to local and international standards.With the aim of determining how cartography represents health services and analyzes them, the research relied on the geographic information systems program as a technological age in the field of geographic and service research.